A rare case of invasive mucormycosis with thrombosis of cerebral vasculature in diabetic ketoacidosis - Sardar, Shahitha; Srinivasan, Suseendhran; Shanmugam, Samuthiravel; Mohanan, Jagadeesan; Suthakaran, Prasanna Karthik; Jeyachandran , Damodaran (International Journal of Advances in Medicine, 2024)
Mucormycosis is a rare fungal infection. It is an aggressive angio invasive infection hence if left untreated is always fatal. This necrotising infection commonly involves the nose, paranasal sinuses, orbits and brain. Uncontrolled diabetes, immunosuppression, transplant recipients, COVID-19 infection are the commonest risk factors. Most common form is rhino orbital cerebral involvement. Antifungal agents along with surgical debridement is the mainstay of treatment. We are reporting such a case of invasive mucormycosis in a young diabetic male to stress the importance of clinical examination and early recognition of clinical signs of this rare invasive infection and aggressive management.